KLITIK PRONOMINA BAHASA DAWAN - Naniana Nimrod Benu (Program Magister Linguistik Universitas Udayana, 2014)
The study of Dawanese pronominal clitics is analyzing the function and distribution of pronominal clitics which is productive in Dawanese from morphosyntactic point of view. Pronominal clitic in this paper refers to a bound form of pronoun in which morphologically attached to other category as its host, but syntactically, it is considered as a free pronoun. Dawanese pronominal clitics is being considered as syntactically free based on two characteristic of clitics that they functioned in a clause as the subject on intransitive and transitive or the direct object of a clause, and having the possessive relation within a noun phrase. The result of analysis shows that there are two types of clitics: proclitics and enclitics. Based on forms, Dawanese prominal clitics consist of asyllabic and syllabic clitics. Based on its meaning, they functioned as subject, object, possessive, and reflexive pronominal clitic. Dawanese clitics can also function to derive a grammatical such as noun or adjective to verb and can be attached to another grammatical category, such as verbs to refer to the subject and object of a clause, to a noun or noun phrase to show the possession, to an adjective that it refers to or describing the noun it modifies, and to a preposition as referring to the subject.